The Use of Leeches in the Management of a Ring Avulsion Injury - Güven, H.; Akbaş, H. (My University, 2002)
Ring avulsion injury presents a spectrum of injury and the treatment varies accordingly from simple suture to amputation. In the current patient, we present a case that has a ring avulsion injury with intact bones, pulleys, flexor tendons, and one digital artery. The problems were venous insufficiency on nearly total avulsed skin and mallet type deformity due to extensor tendon laceration. The avulsed finger skin was sutured in place with interrupted skin sutures and leeches were applied to relieve venous congestion. The result was satisfactory. © Springer-Verlag 2002.
Keywords: Leech; Mallet Type Deformity; Ring Avulsion Injury